Overview of stage characterization in Brazil: training, specializations, and the Job Market (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
In this article, an overview of stage characterization in Brazil is outlined based on the meetings held between 2020 and 2024. The aim is to understand and define the term through the theories of Patrice Pavis and the testimonies of artists interviewed during the Characterization Meetings held by the Laboratório de Caracterização e Adereços and the extension project Núcleo de Criação of Theater School at the Federal University of the Rio de Janeiro. The analysis covers training, the required specializations in characterization for audiovisual and performing arts, as well as the challenges and advancements in the job market.
Keywords: characterizers; characterization; makeup artists; visuality